Assessing Halal Awareness and Lifestyle on Decisions to Stay at Sharia Hotels - Linda Dewi Martiasari; Achsania Hendratmi (Universitas Airlangga, 2022)
ABSTRAK Penelitian ini dikembangkan untuk menganalisa faktor yang mempengaruhi keputusan menginap seorang konsumen muslim terhadap Hotel Syariah. Pengambilan data dilakukan pada tahun 2021 dengan 200 responden dengan menggunakan metode purposive sampling. Dari hasil analisa regresi berganda halal awareness dan lifestyle seorang konsumen muslim berpengaruh signifikan dengan keputusan menginap di Hotel Syariah. Dengan demikian, penelitian ini mengungkapkan pentingnya para pelaku bisnis Hotel Syariah untuk menyusun strategi yang sesuai dengan halal awareness dan lifestyle pasar sasaran seorang konsumen muslim. Kata Kunci: Halal awareness, lifestyle, keputusan pembelian, Hotel Syariah. ABSTRACT This study was developed to analyze the factors that influence the decision to stay at a sharia hotel consumer. Data collection was carried out in 2021 with 200 respondents using the purposive sampling method. From the results of multiple regression analysis, halal awareness and lifestyle of a Muslim consumer have a significant effect on the decision to stay at a sharia hotel. Thus, this study reveals the importance of sharia hotel business players to develop strategies that are in accordance with halal awareness and the lifestyle of the target market of Muslim consumers. Keywords: halal awareness, lifestyle, decision to stay, sharia hotel. DAFTAR PUSTAKA Ahmad, N. A., Abaidah, T. N. T., & Yahya, M. H. A. (2013). A study on halal food awareness among Muslim customers in Klang Valley. Proceedings 4th International Conference on Business and Economic Research, 1073–1087. Alam, S. S., Rohani M., & Hisham, B. (2011). Is religiosity an important determinant on Muslim consumer behaviour in Malaysia? Journal of Islamic Marketing, 2(1), 83-96. https://doi.org/10.1108/17590831111115268 Amarul, A., Sukirno, S., & Kurnia, D. (2019). Understanding the awareness of the importance of halal labels to business actors based on range of long business variations. Business and Management Research, 8(1), 17-21. http://dx.doi.org/10.5430/bmr.v8n1p17 Ambali, A. R., & Bakar, A. N. (2013). Halal food andproducts in Malaysia: People's awareness and policy implications. Intellectual Discourse, 21(1), 7-32. Awan, H. M., Siddiquei, A. N., & Haider, Z. (2015). Factors affecting halal purchase intention–evidence from Pakistan’s halal food sector. Management Research Review, 38(6), 640-660. https://doi.org/10.1108/MRR-01-2014-0022 Azam, A. (2016). An empirical study on non-muslim’s packaged halal food manufacturers: Saudi Arabian consumers’ purchase intention. Journal of Islamic Marketing, 7(4), 441-460. https://doi.org/10.1108/JIMA-12-2014-0084 BPS. (2019). Statistik hotel dan akomodasi lainnya di Indonesia 2018. Retrieved from https://www.bps.go.id/publication/2019/04/11/d64817c1f0294f59556bc76b/statistik-hotel-dan-akomodasi-lainnya-di-indonesia-2018.html BPS. (2020). Statistik hotel dan akomodasi lainnya di Indonesia 2019. Retrieved from https://www.bps.go.id/publication/2020/07/03/4206448bd185bf883b73d414/statistik-hotel-dan-akomodasi-lainnya-di-indonesia-2019.html Dewi, M. N. (2015). Pengaruh gaya hidup (lifestyle), harga, promosi terhadap pemilihan tempat tujuan wisata (destination) studi kasus pada konsumen Artojaya Tour & Travel Surabaya. Jurnal Strategi Pemasaran, 3(1), 1-13. Essoo, N., & Dibb, S. (2004). Religious influences on shopping behaviour: An exploratory study. Journal of Marketing Management, 20(7-8), 683-712. https://doi.org/10.1362/0267257041838728 Ghozali, I. (2011). Aplikasi analisis multivariate dengan program IBM SPSS 19. Semarang: Badan Penetrbit Undip. Haque, A., Chowdhury, N. A., Yasmin, F., & Tarofder, A. K. (2019). Muslim consumers’ purchase behavior towards shariah compliant hotels in Malaysia. Vidyodaya Journal of Management, 5(1), 121-138. https://doi.org/10.31357/vjm.v5i1.3918. Kotler, P., & Keller, K. L. (2012). Manajemen pemasaran. Jakarta: Erlangga. Kotler, P., & Keller, K. L. (2016). Marketing management. London: Pearson Education, Inc. Kotler, P. (2008). Manajemen pemasaran. Jakarta: Indeks. Kotler, P. (2014). Manajemen pemasaran. Jakarta: Prenhalindo. Lutfi, B. A. (2020). Analisis faktor yang memengaruhi preferensi konsumendalam memilih hotel berbasis syariah di kota Malang. Jurnal Ilmiah Mahasiswa FEB, 8(2), 1-11. Mohamed, Z. Rezai, G., Shamsudin, M. N., & Chiew, F. C. E. (2008). Halal logo and consumers’ confidence: What are the important factors. Economic Technology Management Review, 3, 37-45. Mokoagouw, M. L. (2016). Pengaruh lifestyle, harga, kualitasproduk terhadap keputusan pembelian handphone samsung di samsung mobile IT center Manado. Jurnal Berkala Ilmiah Efisiensi, 16(1), 493-502. Mowen, J., & Minor, M. (2002). Perilaku konsumen. Jakarta: Erlangga. Muslichah, M., Abdullah, R., & Razak, L. A. (2019). The effect of halal foods awareness on purchase decision with religiosity as a moderating variable: A study among university students in Brunei Darussalam. Journal of Islamic Marketing, 11(5), 1091-1104. https://doi.org/10.1108/JIMA-09-2017-0102 Muthoifin. (2015). Fenomena maraknya hotel syariah: Studi efektifitas, existensi, dan kesyariahan Hotel Syariah di surakarta. Prosiding University Research Colloquium, 93-106. Nitisusastro, M. (2012). Perilaku konsumen dalam perspektif kewirausahaan. Bandung: Alfabeta. Nurcahyo, A., & Hudrasyah, H. (2017). The influence of halal awareness, halal certification, and personal societal perception toward purchase intention: a study of instant noodle consumption of college student in Bandung. Journal of Business and Management, 6(1), 21-31. Nurhayati, T., & Hendar, H. (2019). Personal intrinsic religiosity and product knowledge on halal product purchase intention: Role of halal product awareness. Journal of Islamic Marketing, 11(3), 603-620. https://doi.org/10.1108/JIMA-11-2018-0220 Pektaş, F. (2018). The effect of lifestyle on the demand for alternative tourism. Uluslararası Yönetim İktisat ve İşletme Dergisi, 14(1), 187-198. http://dx.doi.org/10.17130/ijmeb.2018137581 Rachmawati, E., Suliyanto, & Suroso, A. (2020). A moderating role of halal brand awareness to purchase decision making. Journal of Islamic Marketing, 13(2), 542-563. https://doi.org/10.1108/JIMA-05-2020-0145 Rahardi, N., & Wiliasih, R. (2016). Analisis faktor-faktor yang mempengaruhi preferensi konsumen terhadap hotel syariah. Jurnal Syarikah: Jurnal Ekonomi Islam, 2(1), 180-192. https://doi.org/10.30997/jsei.v2i1.293 Rozalinda. (2014). Ekonomi Islam. Jakarta: Raja Grafindo. Saputra, N., & Tresnati, R. (2020). Pengaruh kesadaran halal dan pengetahuan produk halal terhadap keputusan pembelian pada wisata halal di Bali. Prosiding Manajemen, 6(1). Setiadi, N. J. (2003). Perilaku konsumen: Konsep dan implikasi untuk strategi dan penelitian pemasaran. Jakarta: Kencana. Setiadi, N. J. (2010). Perilaku konsumen. Jakarta: Kencana Prenada Media Group. Setyaningsih, E. D., & Marwansyah, S. (2019). The effect of halal certification and halal awareness through interest in decisions on buying halal food products. Syiar Iqtishadi: Journal of Islamic Economics, Finance and Banking, 3(1), 65-79. Sujarweni, V. W. (2014). SPSS untuk penelitian. Yogyakarta: Pustaka Baru. Sulastiyono, A. (2011). Seri manajemen usaha jasa sarana pariwisata dan akomodasi manajemen penyelenggaraan hotel. Bandung: Alfabeta. Sumarwan, U., Jauzi, A., Mulyana, A., Karno, B. N., Mawardi, P. K., & Nugroho, W. (2011). Riset pemasaran dan konsumen seri 1. Bogor: IPB Press. Suprapti, N. W. S. (2010). Perilaku konsumen: Pemahaman dasar dan aplikasinya dalam strategi pemasaran. Bali: Universitas Udayana Bali. Swidi, A., Cheng, W., Hassan, M. G., Al-Hosam, A., & Mohd Kassim, A. W. (2010). The mainstream cosmetics industry in Malaysia and the emergence, growth, and prospects of halal cosmetics. Proceedings of Third International Conference on International Studies, 1-20. Yunus, N. S. N. M., Rashid, W. E. W., Ariffin, N. M., & Rashid, N. M. (2014). Muslim's purchase intention towards non-Muslim's Halal packaged food manufacturer. Procedia-Social and Behavioral Sciences, 130, 145-154.